The Mimallonidae (Lepidoptera, Mimallonoidea) of the Caribbean Basin, with the descriptions of two new species - R. A. St.Laurent; T. L. McCabe (Zootaxa, 2016)
Mimallonidae of the Caribbean Basin are discussed, with attention primarily given to species endemic to the Caribbean islands and the northern coast of Venezuela. The Caribbean Basin is a political term for tropical regions circumscribed by the Gulf of Mexico. Cicinnus bahamensis sp. n. is described from the Bahamas, the first species of Mimallonidae from this country. The Cuban species Cicinnus packardii (Grote, 1865), the closest relative of C. bahamensis sp. n., is figured and compared. A third, similar, species from northern coastal Venezuela, C. falcoargenteus sp. n., is described and compared to the previous two species.
Keywords: Bahamas; Caribbean Basin; Cicinnus; Cuba; Lepidoptera; Mimallonidae; Venezuela